Development of Belajar Astronomi: an Astronomy Learning Application for Kids - Muharram, Riza Miftah; Budiman, Ade Surya (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Learning process should be an interesting process, especially for kids in elementary school. There are many methods has delivered to make the kids going fun to learn any new thing. Information and Communication Technolgy (ICT) could been involved to the learning process. ICT-based learning tools that used to help teachers and parents are developed in this research. Astronomy is one of the fields of science which is generally taught in schools as a part of natural science subject. In this study, authors developed an astronomy learning application’s named Belajar Astronomi that comes as a supplement study material for elementary students. This Astronomy Learning application is designed to be a tool for students to study astronomy independently. Belajar Astronomi’s application developed with the Visual Basic programming language in Microsoft Visual Studio 2010 using Waterfall methods, to make sure Its functionality and usefulness. The application is equipped with images, text, and videos that can help students to learn astronomy more easily, Its also equipped with quizzes as training materials that can help students in sharpening their knowledge in Astronomy subject.